Effect of butt welded prameters on tensile strength of two plates of CT38 steel - Vu , Văn Khánh; Nguyen, Hồng Thanh; Hoang , Trọng Ánh; Ngo , Mạnh Hà (Journal of Technical Education Science, 2019)
Today, welding technology is widely applied in all areas such as shipbuilding, steel structure fabrication, railway and steel bridge construction. However, welding often appears residual stress and deformation due to irregularity of heating and cooling. This is the direct impact on the durability and working life of the weld structure, especially in the heat-affected area (AHN). This paper studies the effect of manual arc welding (SMAW) parameters on the ultimate tensile strength in the AHN zone and the welded zone (KLMH) when welding the two steel plates CT38. Realizing that the flow limit and the durable limit of the metal in the heat-affected zone depend on the number of layers and the highest value is 589MPa and 685 MPa, respectively, when welding current Ih=120A, the gap g=3mm and number of welding layers n=4. The welding current is the parameter that directly affects the mechanical properties. The yield strength and tensile strength in this zone reach the highest value when welding current Ih=120A, the gap g=5mm, the number of welding layers n=6 with the corresponding values ​​759MPa and 880MPa respectively.